2010
DOI: 10.1007/s10495-010-0513-9
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-induced apoptosis of human melanoma cells involves activation of caspase-4

Abstract: Although it is conventionally regarded as an inflammatory caspase, recent studies have shown that caspase-4 plays a role in induction of apoptosis by endoplasmic reticulum (ER) stress. We report here that activation of caspase-4 is also involved in induction of apoptosis by TNF-related apoptosis-inducing ligand (TRAIL) in human melanoma cells. Treatment with TRAIL resulted in activation of caspase-4. This appeared to be mediated by caspase-3, in that caspase-4 was activated later than caspase-8, -9, and -3, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Increased expression of MMPs was closely correlated with tumor invasion and metastasis [33−36]. CASP4 was upregulated after HIC-1 activation, which is an apoptosis-related cysteine peptidase [37], [38]. BIK, which is a BCL2-interacting killer related to apoptotic induction, was also upregulated [39−42].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of MMPs was closely correlated with tumor invasion and metastasis [33−36]. CASP4 was upregulated after HIC-1 activation, which is an apoptosis-related cysteine peptidase [37], [38]. BIK, which is a BCL2-interacting killer related to apoptotic induction, was also upregulated [39−42].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-4 was recently shown to be involved in TRAIL-induced apoptosis of human melanoma cells. However, inhibition of caspase-4 partially, but not completely, blocked apoptosis (39), suggesting that its role is limited. Since caspase-4 has been shown to be activated later than caspase-8, caspase-9 and caspase-3 (39), it is possible that caspase-4 and caspase-12 may play roles in different processes/stages in ER stress-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, inhibition of caspase-4 partially, but not completely, blocked apoptosis (39), suggesting that its role is limited. Since caspase-4 has been shown to be activated later than caspase-8, caspase-9 and caspase-3 (39), it is possible that caspase-4 and caspase-12 may play roles in different processes/stages in ER stress-induced apoptosis. Our preliminary attempt to establish caspase-12 gene knockdown cells was hampered by considerable cell death in the resting state.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, caspase-4, located on the outer membrane of the endoplasmic reticulum, has been found to be involved in stress-related apoptosis of the endoplasmic reticulum (1618). In addition, some studies also indicated that caspase-4 plays an important role in the TRAIL-induced apoptosis (19,20). …”
Section: Discussionmentioning
confidence: 99%